Omentalização prostática em cãse - Apparício, Maricy [UNESP]; Vicente, Wilter Ricardo Russiano [UNESP]; Pirez, Eliandra Antônia [UNESP]; Mostachio, Giuliano Queiroz [UNESP]; Ribeiro, Ana Paula Coelho [UNESP]; Covizzi, Gabriela Jayme [UNESP]; Gadelha, Carla Renata Figueiredo [UNESP]; Carvalho, Marileda Bonafim [UNESP] (My University, 2006)
The prostate is the only acessory sex gland in the male dog and, although the prostate is found in all mammals, it has a great importance in men and dogs due to the frequency of disorders. Several techniques have been employed for the treatment of prostatic cysts and abscesses and, a few years ago, it was successfully described the use of prostatic omentalisation for this purpose; until now, there are no data about this surgery in Brazil. So, the aim of this study was to evaluate the animal recovery, as well as the post operative period of dogs that underwent prostatic omentalisation, from 2002 to 2004. It was evaluated 11 dogs with prostatic cysts, 4 dogs with prostatic abscesses and 2 with paraprostatic cysts. Fifteen dogs had an uneventful recovery while one dog had a minor incontinence for two days. One dog died due to a previous long term sepsis. The low incidence of post operative complications and brief hospitalization period make omentalisation the surgery of choice for the treatment of prostatic cysts and abscess.
Prostatic omentalisation in dogs
Keywords: Abscess; Cyst; Dogs; Omentalisation; Prostate; Animalia; Canis familiaris; Mammalia